Reliability and validity of the dutch eating behavior questionnaire in an online format for university students from low-income regions in a pandemic context: A 24 hour MESYN study - de Carvalho, Millena Vaz; Cardoso, Antonio Gibran de Almeida; Feuerstein, Shirley Cunha; Sousa, Rosana Rodrigues de; Collese, Tatiana Sadalla; Torres-Leal, Francisco Leonardo; Nascimento-Ferreira, Marcus Vinicius; De Moraes, Augusto Cesar Ferreira (Frontiers in Epidemiology, 2023)
Objective: To test the reliability and validity of the Dutch Eating Behavior Questionnaire (DEBQ), in an online format, on university students from low-income regions. Methods: This was a feasibility and validity study. We applied the questionnaire to a sample of 195 and 117 university students from a low-income region (Gini index of 0.56) to study the validity and reliability, respectively. The DEBQ consists of 33 items on eating behavior distributed into three dimensions: emotional intake, food restriction and external intake. The answers are based on a 5-point Likert scale (never = 1 to very often = 5). We collected the data at two time points, with the application of the same questionnaire and a two-week interval (test-retest). We tested the reliability via test-retest of the questionnaire and construct validity (structural) via exploratory factor analysis. Results: For reliability, we identified an acceptable Spearman correlation coefficient (rho> 0.30 and p <0.05), ranging from 0.44 (p <0.001, Item 33) to 0.84 (p <0.001, Item 31). For construct validity, we identified the three original factors (emotional intake, food restriction and external intake) and three additional factors (impulsive intake, nonimpulsive intake and intake by visual or sentimental influence), with an explained variance of 69.1%. Conclusion: The online format of the DEBQ has acceptable reliability and validity for measuring the construct of eating behavior in university students from low-income regions.